Augustus : first emperor of Rome - Goldsworthy, Adrian Keith (New Haven : Yale University Press, 2014)
The dramatic story of Rome's first emperor, who plunged into Rome's violent power struggles at the age of nineteen, proceeded to destroy all rivals, and more than anyone else created the Roman Empire Caesar Augustus' story, one of the most riveting in Western history, is filled with drama and contradiction, risky gambles and unexpected success. Thrusting himself into Rome's extremely violent politics while yet a very young man, Augustus skillfully maneuvered his way through twisting alliances during years of civil war. Named heir to the murdered Julius Caesar, he outwitted and outlasted far more experienced rivals like Antony and Brutus. Ruling supreme, he reinvented himself as a benevolent man of peace and created a new system of government. In this highly anticipated biography Goldsworthy puts his deep knowledge of ancient sources to full use, recounting the events of Augustus' long life in greater detail than ever before. Goldsworthy pins down the man behind the myths: a consummate manipulator, propagandist, and showman, both generous and ruthless. Under Augustus' rule the empire prospered, yet his success was never assured and the events of his life unfolded with exciting unpredictability. Goldsworthy captures the passion and savagery, the public image and private struggles of the real man whose epic life continues to influence Western history.
Tells the story of the heir to the murdered Julius Caesar who, as Rome's first emperor, brought peace and stability to the empire and presided over a new system of government.
Caius Octavius (Thurinus), 63-44 BC. 'Father of his country' ; 'A man of wealth and good reputation' ; The consulship of Julius and Caesar ; A way out -- Caius Julius Caesar (Octavianus), 44-38 BC. Heir ; Praise ; Reward and discard ; Vengeance and discord -- Imperator Caesar, Divi Filius, 38-27 BC. Sons of gods ; Rivals ; Triumph -- Imperator Caesar Augustus, Divi Filius, 27-2 BC. Renewal and restoration ; To overcome the proud in war ; The 'title of greatest power' ; The eagles ; An end and a beginning ; Family and colleagues ; Augustan peace -- Imperator Caesar Augustus, Divi Filius, Pater Patriae, 2 BC-AD 14. Father ; The 'sentry post' ; For the sake of the Res Publica ; Pax Augusta -- Hurry slowly -- Appendix 1. The senatorial career, or, Cursus Honorum -- Appendix 2. Date of the birth of Jesus.
Includes bibliographical references (pages 522-586) and index.
Keywords: Augustus, -- Emperor of Rome, -- 63 B.C.-14 A.D.; Emperors -- Rome -- Biography; Rome -- History -- Augustus, 30 B.C.-14 A.D.